Greater Competitiveness in Recruitment and Selection Processes, Better User Satisfaction? Evidence from Public Services of the Chilean State - Valdebenito, Sebastián; Pliscoff, Cristian (Revista del CLAD Reforma y Democracia, 2023)
Does competitive examination as a means of selecting civil servants entering the public administration affect user satisfaction? This article seeks to develop this issue within the framework of a discussion on the impact of merit in the management of the State. Latin American public administrations are undergoing sustained change to install processes in their people management practices. In doing so, they seek to leave behind clientelistic or discretionary practices and install selection mechanisms that favor merit to access any public office. The figures show progress in this area, although there is still much room for improvement. This paper manages information from the Chilean public agencies regarding the use of competitive bidding, associating it with user satisfaction, which has been systematically measured in the public administration in recent years. The results of this study confirm a positive relationship between the levels of competitive examinations and user satisfaction, suggesting that a more meritocratic selection in public competitions of civil servants implies better management and performance in their organizations. Finally, conclusions referring to the Chilean case are presented, which may be helpful for other public administrative systems in Latin America.
Keywords: Civil Service; Personnel Recruitment; Personnel Selection; Merit System; Public Services; Competitiveness; Relations with Costumers; Chile